Predictive Capacity of ACEF Score to Detect All-Cause Mortality and Post Contrast Acute Kidney Injury Among PCI Patients - Karki, Parag; Maskey, Arun; Timalsena, Birat Krishna; Poudel, Samir Kumar; Gautam, Binayak; Pant, Shambhu; Budhathoki, Lee (Nepalese Heart Journal, 2020)
Background and Aims: ACEF score is simple risk score which uses only three parameters for predicting mortality and postcontrast acute kidney injury (PC-AKI). This study was designed to look into various risk factors and ACEF score for patients undergoing Percutaneous Coronary Intervention (PCI).Methods: This is single-centre, observational, cross-sectional study. The patients were divided into tertiles.Bivariate analysis of various risk factors and ACEF score was done for PC-AKI as well as In-hospital and 30-day mortality.Results: Total 257 patients were included.The total mortality among PCI patients were low: In-hospital (0.8%) and 30-day (1.9%). The risk factor for increased mortality were higher Killip class and reduced Ejection Fraction (EF). PCAKI occurred in one-fifth. The risk factors for PC-AKI were increasing age, higher Killip class, diabetes, reduced EF, emergency PCI procedure and higher contrast volume. Hydration with NS was protective against PC-AKI. Mean ACEF score was higher among those who died within 30 days (p=0.35) and who developed PC-AKI (p